SISTEM PAKAR IDENTIFIKASI GANGGUAN ORGANISME PENGGANGGU TANAMAN DAN DEFISIENSI HARA TANAMAN HIAS KRISAN - Pramurjadi, Andy; Arsanti, Idha W; Gartina, Dhani; Budiarto, Kurniawan (Informatika Pertanian, 2017)
Pests and nutrient are important growth environment that influence the quality of chrisanthemum flowers.  Physical damages and poor plant growth qualities reduce the quantity and quality of the flower product.  The variety of pests and physiological disturbance of plants due to nutrient deficiency requires an accurate identification device. Such device is needed determine the main cause of abnormalitiessymptom in plant, so that it can be acurately and rapidly managed. Expert systems that provide knowledge-based interactive information for pest identification and nutrient deficiency are alternative tools that can diagnose such physical symptoms.   The result of  evaluation showed that the system gives certain level potential acuracy..  Element that need  attention to improve the exepert system is the completeness of visual  test materials, i.e.,plant image that represent the pest attacks and nutritional deficiencies symptoms.